Financial market integration in Europe: on the effects of EMU on stock markets - Marcel Fratzscher (European Central Bank (ECB), 2001)
This paper analyzes the integration process of European equity markets since the 1980s. Its central focus is on the role that EMU, and specifically, changes in exchange rate volatility, has played in this process of financial integration. Building on an uncovered interest rate parity condition to measure financial integration, a trivariate GARCH model with time-varying coefficients yields three key results: first, European equity markets have become highly integrated only since 1996. Second, the Euro area market has gained considerably in importance in world financial markets and has taken over from the US as the dominant market in Europe. And third, the integration of European equity markets is in large part explained by the drive towards EMU, and in particular the elimination of exchange rate volatility and uncertainty in the process of monetary unification
Keywords: C32; F3; G15; 330